2007
DOI: 10.1176/appi.ajp.2007.06111792
|View full text |Cite
|
Sign up to set email alerts
|

Affective Disorders and Cognitive Failures: A Comparison of Seasonal and Nonseasonal Depression

Abstract: Seasonal depression shares certain common symptoms with nonseasonal depression; however, the two disorders have never been examined in a single study, to the authors' knowledge. The goal of this research was to examine the potential similarities in cognitive impairments in seasonal affective disorder and major depressive disorder in college students in the Midwest. Identification of affective disorders was based on participants' self-reported behavior and affect on the Beck Depression Inventory and the Seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 22 publications
3
36
1
1
Order By: Relevance
“…Early studies on cognitive failures and anxiety showed that there existed a significant positive relationship between cognitive failures and anxiety (Broadbent et al, 1982). Studies also showed a meaningful relationship between cognitive failures, anxiety, psychological tension and affection disorders (Sullivan & Payne, 2007). CFQ scores had been found to be positively correlated with state anxiety symptoms even after controlling for the influence of trait anxiety and neuroticism (Merckelbach, Muris, Nijman, & de Jong, 1996), although there had been a significant association between CFQ scores and trait anxiety (Smith, Chappelow, & Belyavin, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies on cognitive failures and anxiety showed that there existed a significant positive relationship between cognitive failures and anxiety (Broadbent et al, 1982). Studies also showed a meaningful relationship between cognitive failures, anxiety, psychological tension and affection disorders (Sullivan & Payne, 2007). CFQ scores had been found to be positively correlated with state anxiety symptoms even after controlling for the influence of trait anxiety and neuroticism (Merckelbach, Muris, Nijman, & de Jong, 1996), although there had been a significant association between CFQ scores and trait anxiety (Smith, Chappelow, & Belyavin, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia was found to be a significant predictor of each of these factors: memory (b = 0.29, t(894) = 9.28, p \ .001, b = 0.29), distractibility (b = 0.33, t(903) = -8.92, p \ .001, b = 0.29), blunders (b = 0.26, t(896) = 9.14, p \ .001, b = 0.29), and (memory for) names (b = 0.05, t(917) = 4.35, p \ .001, b = 0.14). It has previously been reported that cognitive functioning has a significant relationship with depression (Merckelbach et al 1996;Sullivan and Payne 2007), stress (Mahoney et al 1998), and anxiety (Houston 1989;Matthews and Wells 1998). Therefore, we next conducted a multiple regression model in which the CFQ was predicted by the ISI, along with the QIDS, PSS, PANAS, and STAI.…”
Section: Resultsmentioning
confidence: 99%
“…Merckelbach et al (1996) found cognitive failures to be related to depression in a sample of Dutch students. Similarly, Sullivan and Payne (2007) found cognitive failures were significantly greater in a sample of college students with seasonal affective disorder and major depressive disorder than non-depressed college students. Mahoney et al (1998) found stress and anxiety were strongly associated with self-reported and observed cognitive failures in individuals aged 16-29.…”
mentioning
confidence: 83%
“…Sullivan and Payne (2007) stated that the relationship between cognitive failures, anxiety, and psychological tension (29). When anxiety is increased, perception and attention are worse affected (7,30).…”
Section: Discussionmentioning
confidence: 99%